PENGARUH PENERAPAN E-FILING, PENGETAHUAN PERPAJAKAN, DAN KESADARAN WAJIB PAJAK TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK DENGAN KUALITAS PELAYANAN PAJAK SEBAGAI VARIABEL MODERASI (Studi Kasus KPP Pratama Lamongan) - DIANATUL FITRIYAH; ISNAINI RASYIDA ANNISWATI; HAVE ZULKARNAEN (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to examine the influence of e-filing, tax knowledge, and taxpayer awareness on taxpayer compliance, with tax service quality as a moderating variable. Data were collected through questionnaires distributed to 100 individual taxpayers at KPP Pratama Lamongan. The analysis was conducted using Structural Equation Modeling (SEM-PLS) with SmartPLS 4.0. The findings show that e-filing, tax knowledge, and taxpayer awareness have a significant positive effect on compliance. However, tax service quality only moderates the relationship between tax knowledge and compliance, while other moderating effects are not significant. These results imply the importance of enhancing tax literacy, optimizing digital systems, and improving service quality.